A novel method of creation of a fenestration in nitinol occluder devices used in closure of hypertensive patent arterial ducts - Anil Kumar Singhi; Kothandam Sivakumar (Wolters Kluwer Medknow Publications, 2016)
Test occlusion with a balloon is done to predict operability of large hypertensive patent ductus arteriosus (PDA). If the fall in the pulmonary artery pressures is inadequate, a complete closure is not desired. To create a predictable premeasured fenestration in a nitinol occluder device used for closing hypertensive PDA. A large nitinol occluder device was punctured with an 18G needle to advance a 0.035½ stiff guide wire through the occluder before loading it into the delivery system. The occluder with the guidewire was then deployed across the PDA. A coronary guide catheter was later threaded through the guidewire into the fabric of the device, which was still held by the delivery cable. A coronary stent was deployed across the fenestration in the occluder to keep it patent. An 8-year-old boy with Down syndrome and hypertensive PDA was hemodynamically assessed. Even though there was a fall in the pulmonary vascular resistance index and pressures on test occlusion, the pulmonary artery pressures were labile with fluctuations. A customized fenestration was made in a 16 mm muscular ventricular septal defect occluder (MVSO) with a 4.5 mm bare-metal coronary stent. The pulmonary artery pressures remained at half of the aortic pressures after the procedure. This fenestration model precisely and predictably fenestrated a large occluder device used to close a hypertensive large PDA. Long-term patency of these fenestrations has to be assessed on the follow-up, and may be improved through larger fenestrations, systemic anticoagulation and use of covered stents.